Improving innovation in construction projects: Knowledge-sharing, open-mindedness and shared leadership - Mohsin Ali Soomro; Ahsan Ali; Aftab Hameed Memon; Shabir Hussain Khahro; Zubair Ahmed Memon (Journal of Innovation & Knowledge)
In the dynamic world of construction projects, fostering innovation is paramount. This study investigates the transformative potential of shared leadership as a catalyst for team innovation. We examine knowledge-sharing density as a critical mediator through the lens of knowledge management. We adopted a mixed methods approach, collecting multi-wave and multi-source field data and using social network measures. The results demonstrate shared leadership acts as a direct driver of knowledge-sharing density, facilitating innovation in construction projects. Knowledge-sharing density emerges as a transformative force, mediating the impact of shared leadership on team innovation. This intricate relationship unveils hidden potential for innovation within construction teams. Results also show the influence of team open-mindedness norms, which moderate the direct link between knowledge-sharing density and team innovation and the indirect influence of shared leadership. This study pioneers an integrated approach to understanding leadership and knowledge management in the construction sector, with important insights for team leadership, knowledge-sharing, and project performance.